The Discrete Time-Space SIR-SI Age-Structured Model for Leptospirosis - Samat, Nor Azah; Awang, Aznida Che (International Journal of Engineering and Technology, 2018)
The aim of this study is to introduce new discrete time-space SIR-SI age-structured disease transmission models for Leptospirosis disease. The term â€œage-structuredâ€ here refers to having two different age groups, which are children and adult. These models are important because it will later lead to a conclusion of whether children or adult have high risk of being infected by Leptospirosis disease. In this study, two types of SIR-SI age-structured models are introduced. These include models with and without the transition rate between age groups. The future application of these two models will be based on the availability of parameter value and Leptospirosis data.